The experience of women in hospital rest with preterm premature rupture of de amniotic membranes - María del Mar Fernández Míguez; Aránzazu Domínguez Luna; Mónica Rojo López (Fundación para el Desarrollo de la Enfermería, 2012)
Hospital bed rest in a preterm premature rupture of the amniotic membranes involves a crisis situation for women with very high emotional effects.To understand the needs felt of the gestantes with pregnancies of high risk on the part of the professionals, it will improve the quality of the attention and it can help to diminish the stress levels at this vulnerable period and to confronting the maternity.Aim: Investigate women´s experience when they are resting in hospital in cases de preterm premature rupture of membranes.Methodology: Phenomenological study, It has taken as a population of study to women hospitalized in the plant of obstetrics of high risk from Gregorio Marañón Hospital, with preterm premature rupture of membranes between 24 and 31 weeks of gestation.Data collection: Was be carried out by means of the individual interviews in hospitable environment; observation and withdrawal of notes during the accomplishment of this one.